Unveiling the complete organelle genomes of Gypsophila vaccaria: de novo assembly and evolutionary insights into a medicinally important species - Zhang, Chaoqiang; Yang, Ruifeng; Wang, Mengyue; Zhang, Jiayin; Shen, Jingting; Yang, Bin; Zhang, Dongzhi; Yin, Liang; Wang, Xiaoming; Huang, Chien-Hsun; Li, Jinglong (Frontiers in Plant Science, 2025)
IntroductionGypsophila vaccaria (Caryophyllaceae) is a medicinal plant with over 2,000 years of documented use in China. Despite its known pharmacological properties and phytochemical profile, no organellar genomic resources are currently available, limiting evolutionary studies and molecular breeding efforts.MethodsWe assembled the complete mitochondrial (361,814 bp) and quadripartite chloroplast (150,050 bp) genomes of G. vaccaria using HiFi sequencing. Codon usage, RNA editing, and selection pressure were analyzed, and phylogenomic relationships were inferred. Species-specific SSR markers were identified for potential molecular applications.ResultsHiFi-based assembly revealed exceptional mitochondrial genome plasticity, with 15.6% (56.7 Kb) derived from chloroplast DNA transfers—the highest reported in Caryophyllaceae—including 12 functional genes (e.g., rps7, ndhB, rrn16S). Both organellar genomes show A/U-biased codon usage (mitochondrial RSCU: 29/44 codons) and divergent RNA editing (257 mitochondrial vs. 105 chloroplast C-to-U sites). Positive selection (Ka/Ks > 1) was detected in cytochrome c maturation genes (ccmFN, ccmB, ccmFC), contrasting with overall purifying selection (median ω = 0.32). Phylogenomic analyses robustly resolved Caryophyllaceae–Amaranthaceae sisterhood (BS = 100%).DiscussionAs the first organellar genomes from Gypsophila, this study provides insights into lineage-specific adaptations through chloroplast-mitochondrial co-evolution. The 56.7 Kb MTPTs and positively selected cytochrome c genes serve as targets for adaptive evolution research, while 81 species-specific SSRs facilitate molecular marker development in Caryophyllaceae.